Honra, prudência e justiça na obra política de Thomas Hobbes - Silveira, Ricardo dos Reis (2010)
The work of Thomas Hobbes, based on the Renaissance concepts, builds a new political philosophy which results in original concepts of the state, rights and justice. This thesis focus on Thomas Hobbes most relevant political works: The Elements of Law, Natural and Politic; De Cive and Leviathan to show that the use of a contract, or an agreement enforceable by law, results in a new law concept which the sovereign power is established by the wishes of the individuals. The analysis starts with Hobbes ideas as opposed to the Aristotelic thinking of the politics and the human nature. A critical examination is performed on how Hobbes thinking approached the mechanistic theses, the actual need of these theses to the foundation of his work and finally the main impacts of Hobbes s political works. The examination also explores the concept of honor, prudence, the individual-state relationship and the controversies about justice in the Theory of Plato, Aristotle, Hobbes and Christian. It is concluded that Hobbes's work is among the greatest legacy to the modern States and has a deep influence on the political organizations.